Embolic Stroke of Undetermined Source (ESUS): Exploring the Neurocardiological Axis and Its Clinical Implications - Gabriela Dumachita Sargu; Roxana Covali; Cristiana Filip; Tudor Butureanu; Mona Akad; Ioana Păvăleanu; Andrei Ionuț Cucu; Amelian Mădălin Bobu; Laura Riscanu; Diana Lacatusu; Madalina Irina Smihor; Radu Popa (Medicina)
Embolic stroke of undetermined source (ESUS) was proposed in 2014 as a clinical category to subgroup non-lacunar cryptogenic ischemic strokes that appear embolic but lack an identifiable cause despite thorough investigation. The initial hypothesis was that anticoagulation might offer superior secondary prevention compared to antiplatelet therapy, prompting several large clinical trials. This review synthesizes current knowledge on ESUS. ESUS represents about 17% of ischemic strokes and often affects younger patients with fewer traditional risk factors. Although these patients lack major cardioembolic sources (e.g., atrial fibrillation) or significant arterial stenosis, many have covert embolic substrates. Major trials—NAVIGATE ESUS, RE-SPECT ESUS, and the atrial cardiopathy-focused ARCADIA—found no benefit of anticoagulants over aspirin, challenging the original ESUS framework. These results highlight the heterogeneity within ESUS and underscore the need for individualized diagnostic and therapeutic strategies.